Exploring the role of language proficiency and cultural adaptation in travel risk perception: A study of Asian working holiday makers in Australia. (April 2020) - Nagai, Hayato; Tkaczynski, Aaron; Benckendorff, Pierre J
The perceived risk associated with international travel is frequently acknowledged as having a major influence on tourist behaviour. However, the influence of language proficiency and cultural adaptation on risk perception has not been well researched, especially in the context of tourists from non-English-speaking backgrounds. This study explored these influences and associations by focusing on Asian working holiday makers (WHMs) in Australia. It was found that English language proficiency and cultural adaptation were significant predictors of perceived risk. Asian WHMs who had difficulty adapting to the host culture perceived greater levels of risk. However, Asian WHMs with higher language proficiency tended to perceive greater travel risks. The findings have both theoretical and practical implications for the study of risk perceptions and the management of visitors with low language proficiency.